2021
DOI: 10.3390/en14227748
|View full text |Cite
|
Sign up to set email alerts
|

The Subsequent Effects of Soil Pollution by Petroleum Products and Its Bioremediation on the Antioxidant Response and Content of Elements in Vicia faba Plants

Abstract: Petroleum-derived substances (PDSs), which are one of the most significant sources of energy, have become key factors that affect soils and, consequently, plants. The aim of this study was to determine the subsequent effects of soil contamination by PDSs such as petrol (P), diesel fuel (DF) and used engine oil (EO), in addition to its bioremediation using a ZB-01 biopreparation, on the activities of antioxidising enzymes as well as on the content of antioxidants in the leaves of Vicia faba L. The effects on th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 58 publications
1
8
0
Order By: Relevance
“…Petroleum substances affect the chemical composition of crops grown on polluted soils, modifying the content of macronutrients [ 54 , 55 ] and heavy metals in various plant organs [ 25 , 56 , 57 ], and in the soil itself [ 58 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Petroleum substances affect the chemical composition of crops grown on polluted soils, modifying the content of macronutrients [ 54 , 55 ] and heavy metals in various plant organs [ 25 , 56 , 57 ], and in the soil itself [ 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…Petroleum has a negative effect on the growth and development of plants [ 55 , 59 ]. This study demonstrated the stimulating influence of increasing petrol doses on the content of all heavy metals, except copper, in the aerial biomass of maize in the series without material amendments.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Soil contamination with petroleum derivatives, including diesel oil, reduces soil fertility, disturbs soil ecological homeostasis [ 15 ], suppresses the activity and reduces the biodiversity of microorganisms [ 16 ], impairs biochemical cycles and adversely affects plant production [ 17 , 18 ]. When diesel oil pervades the soil, it adversely affects air and water management and reduces the capacity of the soil sorption complex [ 19 , 20 ], as well as distorts the proportions of carbon to nitrogen and phosphorus [ 20 ] and modifies the contents of trace elements in plant organs [ 21 ]. Soil contamination with diesel fuel can also increase the contents of many trace elements in soil, such as cadmium, lead, copper, nickel and manganese [ 20 , 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…When diesel oil pervades the soil, it adversely affects air and water management and reduces the capacity of the soil sorption complex [ 19 , 20 ], as well as distorts the proportions of carbon to nitrogen and phosphorus [ 20 ] and modifies the contents of trace elements in plant organs [ 21 ]. Soil contamination with diesel fuel can also increase the contents of many trace elements in soil, such as cadmium, lead, copper, nickel and manganese [ 20 , 22 , 23 ]. However, its effect on trace element contents in soil depends on the level of diesel pollution, as well as the soil properties [ 23 ].…”
Section: Introductionmentioning
confidence: 99%